Process for the preparation of c2 to c3 hydrocarbons in the presence of a hybrid catalyst

CN116057029BActive Publication Date: 2026-10-27DOW GLOBAL TECHNOLOGIES LLC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202180044022.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-06-30
Filing Date
2021-06-18
Publication Date
2026-10-27
Estimated Expiration
2041-06-18

Smart Images

  • Figure CN116057029B_ABST
    Figure CN116057029B_ABST
Patent Text Reader

Abstract

A process for producing C2 to C3 hydrocarbons can include introducing a feed stream comprising hydrogen and a carbon-containing gas including carbon monoxide, carbon dioxide, and combinations thereof into a reaction zone of a reactor, and converting the feed stream into a product stream comprising C2 to C3 hydrocarbons in the presence of a hybrid catalyst in the reaction zone. The hybrid catalyst can include a metal oxide catalyst component and a microporous catalyst component comprising 8-MR pore openings less than or equal to 6 A and cage defining ring sizes less than or equal to 7 A, wherein a C2 / C3 carbon molar ratio of the product stream is greater than or equal to 0.7.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Cross-references to related applications This application claims priority to U.S. Provisional Patent Application No. 63 / 045,893, filed on June 30, 2020, the entire disclosure of which is hereby incorporated by reference. Background Technology Technical Field

[0003] This specification generally relates to methods for converting a feed stream containing hydrogen and carbon into C2 to C3 hydrocarbons. In particular, this specification relates to methods for converting a feed stream containing hydrogen and carbon into C2 to C3 hydrocarbons using a hybrid catalyst comprising a metal oxide catalyst component and a microporous catalyst component.

[0004] Typically, in hybrid catalyst methods, the feed stream containing hydrogen and carbon, such as syngas (synthesis gas), comprises hydrogen (H2) gas and carbon-containing gas. The hybrid catalysts used in hybrid catalyst methods typically comprise a combination of a mixed metal oxide catalyst component and a microporous catalyst component, such as a molecular sieve, operating in synergistic manner. Background Technology For many industrial applications, hydrocarbons are used or serve as starting materials to produce plastics, fuels, and a variety of downstream chemicals. C2 to C3 hydrocarbons are particularly useful in downstream applications. Numerous methods have been developed for the production of these lower hydrocarbons, including petroleum cracking and various synthetic methods.

[0006] Synthetic methods for converting feed carbon into desired products, such as lower hydrocarbons, are known. However, current hybrid catalyst methods may result in a lower-than-expected C2 / C3 carbon molar ratio in the products.

[0007] Therefore, there is a need for methods and systems, and hybrid catalysts used therein, in which the product stream has a higher C2 / C3 carbon molar ratio, while still having a sufficiently high yield of the desired C2 to C3 hydrocarbons. Summary of the Invention

[0008] Embodiments of this disclosure address this and other requirements by using a hybrid catalyst comprising a metal oxide catalyst component and a microporous catalyst component to convert a hydrogen- and carbon-containing feed stream into C2 to C3 hydrocarbons. The microporous catalyst component comprises an 8-MR pore opening of less than or equal to 5.1 Å and a cage-bound ring size of less than or equal to 7.45 Å, wherein the C2 / C3 carbon molar ratio in the product stream is greater than or equal to 0.7.

[0009] According to an embodiment, a method for preparing C2 to C3 hydrocarbons includes introducing a feed stream containing hydrogen and a carbon-containing gas into a reaction zone of a reactor, the carbon-containing gas comprising carbon monoxide, carbon dioxide, and mixtures thereof; and converting the feed stream into a product stream containing C2 to C3 hydrocarbons in the presence of a hybrid catalyst comprising a metal oxide catalyst component and a microporous catalyst component, the microporous catalyst component comprising an 8-membered ring (MR) pore opening of a size less than or equal to 5.1 Å and a cage-bound ring size less than or equal to 7.45 Å, wherein the C2 / C3 carbon molar ratio of the product stream is greater than or equal to 0.7.

[0010] Further features and advantages will be set forth in the following detailed description, and in part will be apparent to those skilled in the art from those description or will be recognized by practice of the embodiments described herein, including the following detailed description.

[0011] It should be understood that both the foregoing general description and the following detailed description describe various implementation schemes and are intended to provide an overview or framework for understanding the nature and characteristics of the claimed subject matter. Attached Figure Description

[0012] Figure 1 This is a schematic diagram illustrating the flow introduced into the reactor and the resulting product flow leaving the reactor according to one or more embodiments of the present disclosure. Detailed Implementation

[0013] Reference will now be made in detail to an embodiment of a method for converting a feed stream containing hydrogen and a carbon-containing gas into C2 to C3 hydrocarbons, the carbon-containing gas comprising carbon monoxide, carbon dioxide, and mixtures thereof, wherein the C2 / C3 carbon molar ratio of the product stream is greater than or equal to 0.7. This method uses a hybrid catalyst comprising a metal oxide catalyst component and a microporous catalyst component, the microporous catalyst component comprising 8-MR pore openings of less than or equal to 5.1 Å and cage-bound ring sizes of less than or equal to 7.45 Å. As used herein, the C2 / C3 carbon molar ratio is defined as the ratio of the number of moles of carbon present in the ethylene and ethane streams (in moles per hour) to the number of moles of carbon present in the propylene and propane streams (in moles per hour).

[0014] As used herein, it should be noted that “synthesis gas” and “synthesis gas” are used in this document to refer to a mixture that mainly consists of hydrogen, carbon monoxide, carbon dioxide, and very usually some inert substances.

[0015] The cage-defining ring size is a feature well known to those skilled in the art, and is further described in “Cage-Defining Ring: A Molecular Sieve Structural Indicator for Light Olefin Product Distribution from the Methanol-to-Olefins Reaction,” John Hun Kang, Faisal H. Alshafei, Stacey I. Zones, & Mark E. Davis, ACS Catalysis 2019 9(7), 6012-6019 (April 11, 2019). For topologies that do not form cages, the cage-defining ring size can be applied to that structure. For example, for a topology with an ellipsoidal shape, the equivalent of the cage-defining ring size can be the maximum radius of the ellipsoid.

[0016] Microporous catalysts are known to be used when converting a carbon-containing feed stream into desired products, such as C2 to C3 hydrocarbons. Typically, in some syngas to hydrocarbon processes, it is desirable to achieve high productivity of the desired C2 to C3 hydrocarbons while simultaneously achieving high catalyst activity. However, microporous catalyst components traditionally used in syngas to hydrocarbon processes can result in undesirable low C2 / C3 carbon molar ratios in the products. Specifically, in some syngas to hydrocarbon processes, the objective may be to maximize the amount of C2 hydrocarbons formed. As disclosed and described herein, it has been found that microporous catalyst components comprising 8-MR pore openings of less than or equal to 5.1 Å and cage-bound ring sizes of less than or equal to 7.45 Å can increase the C2 / C3 carbon molar ratio of the products and the amount of C2 hydrocarbons formed. Syngas to hydrocarbon processes with increased C2 / C3 carbon molar ratios in the products according to embodiments will now be described in more detail.

[0017] refer to Figure 1In one embodiment, feed stream 102 is fed into reaction zone 101, and feed stream 102 may contain H2, carbon monoxide (CO), carbon dioxide (CO2), and mixtures thereof. In one or more embodiments, feed stream 102 is syngas. In one embodiment, H2 gas is present in feed stream 102 in an amount of 10 volume percentage (volume %) to 90 volume %, based on the combined volume of H2, CO, and CO2. In another embodiment, H2 gas is present in feed stream 102 in an amount of 40 volume % to 80 volume %, or 60 volume % to 80 volume %, based on the combined volume of H2, CO, and CO2. Feed stream 102 is introduced into reaction zone 101 and contacted with a hybrid catalyst in reaction zone 101. As described in more detail herein, the hybrid catalyst comprises a mixed metal oxide catalyst component and a microporous catalyst component. After feed stream 102 is introduced into reaction zone 101 and contacted with the hybrid catalyst, product stream 103 exits reaction zone 101. Product stream 103 can be separated to form recycle stream 104, which, according to an embodiment, is combined with feed stream 102, or, according to an embodiment, can be introduced into reaction zone 101. Figure 1 (Not shown in the image) to be combined with the feed flow 102.

[0018] As disclosed above, feed stream 102 may contain H2, CO, CO2, or combinations thereof. According to an embodiment, feed stream 102 may contain more than 10.0 vol% of H2, such as 10.0 vol% to 90.0 vol% of H2, 10.0 vol% to 80.0 vol% of H2, 10.0 vol% to 70.0 vol% of H2, 10.0 vol% to 60.0 vol% of H2, 10.0 vol% to 50.0 vol% of H2, 10.0 vol% to 40.0 vol% of H2, or 10.0 vol% to 30.0 vol% of H2. In one embodiment, feed stream 102 contains 20.0 vol% to 90.0 vol% of H2, such as 30.0 vol% to 90.0 vol%, 40.0 vol% to 90.0 vol%, 50.0 vol% to 90.0 vol%, or 80.0 vol% to 90.0 vol% of H2. In one or more embodiments, feed stream 102 contains 20.0 vol% to 80.0 vol% of H2, such as 40.0 vol% to 80.0 vol%, or 60.0 vol% to 80.0 vol% of H2. In another embodiment, feed stream 102 contains 45.0 vol% to 85.0 vol% of H2, such as 55.0 vol% to 85.0 vol%, or 65.0 vol% to 85.0 vol% of H2.

[0019] Unbound by any particular theory, it is believed that the coking and decoking rates are nearly balanced, which could significantly reduce the coking of the hybrid catalyst. This, in turn, allows the hybrid catalyst to remain in reaction zone 101 for extended periods without regeneration. In an embodiment, the hybrid catalyst can be retained in reaction zone 101 without coking for more than 5 hours, such as more than 7.5 hours, more than 10 hours, more than 12.5 hours, more than 15 hours, more than 17.5 hours, more than 20 hours, more than 22.5 hours, more than 25 hours, more than 27.5 hours, or more than 30 hours.

[0020] In one embodiment, product stream 103 may contain C2 to C3 hydrocarbons at a total hydrocarbon fraction greater than 40 C mol%, such as greater than 42 C mol%, greater than 44 C mol%, greater than 46 C mol%, greater than 48 C mol%, or greater than 50 C mol%. In one or more embodiments, the C2 to C3 hydrocarbons are substantially composed of C2 to C3 olefins.

[0021] In an embodiment, the C2 / C3 carbon molar ratio of product stream 103 can be greater than or equal to 1.0. For example, in an embodiment, the C2 / C3 carbon molar ratio of product stream 103 can be greater than or equal to 1.1, greater than or equal to 1.2, greater than or equal to 1.3, greater than or equal to 1.4, or greater than or equal to 1.5. In an embodiment, the C2 / C3 carbon molar ratio of product stream 103 can be less than or equal to 3.0, less than or equal to 2.9, less than or equal to 2.8, less than or equal to 2.7, less than or equal to 2.6, or less than or equal to 2.5. In the implementation scheme, the C2 / C3 carbon molar ratio of product stream 103 can be greater than or equal to 1.0 and less than or equal to 3.0, such as greater than or equal to 1.0 and less than or equal to 2.8, greater than or equal to 1.0 and less than or equal to 2.6, greater than or equal to 1.2 and less than or equal to 3.0, greater than or equal to 1.2 and less than or equal to 2.8, greater than or equal to 1.2 and less than or equal to 2.6, greater than or equal to 1.5 and less than or equal to 3.0, greater than or equal to 1.5 and less than or equal to 2.8, or greater than or equal to 1.5 and less than or equal to 2.6.

[0022] The reaction conditions within reaction zone 101 will now be described. The feed stream 102 may be contacted with the hybrid catalyst in reaction zone 101 under reaction conditions sufficient to form a product stream 103 comprising C2 to C3 hydrocarbons. The reaction conditions include temperatures within reaction zone 101 in the range of 300°C to 500°C, such as 380°C to 450°C, 380°C to 440°C, 380°C to 430°C, 380°C to 420°C, 380°C to 410°C, 380°C to 400°C, or 380°C to 390°C, according to one or more embodiments. In embodiments, the temperature within reaction zone 101 is 390°C to 450°C, 400°C to 450°C, 410°C to 450°C, 420°C to 450°C, 430°C to 450°C, or 440°C to 450°C. In the implementation scheme, the temperature within the reaction zone 101 is 380°C to 450°C, such as 390°C to 440°C, 400°C to 430°C, or 410°C to 420°C.

[0023] In the implementation scheme, the reaction conditions also include a pressure of at least 20 bar (20,000 kPa) within the reaction zone 101, such as at least 25 bar (25,000 kPa), at least 30 bar (30,000 kPa), at least 35 bar (35.00 kPa), at least 40 bar (40,000 kPa), at least 45 bar (45,000 kPa), at least 50 bar (50,000 kPa), at least 55 bar (55,000 kPa), at least 60 bar (60,000 kPa), at least 65 bar (65,000 kPa), or at least 70 bar (70,000 kPa). In the implementation scheme, the reaction conditions include pressures of 20 bar (20,000 kPa) to 70 bar (70,000 kPa) within the reaction zone 101, such as 25 bar (25,000 kPa) to 65 bar (65,000 kPa), or 30 bar (30,000 kPa) to 60 bar (60,000 kPa), 35 bar (35,000 kPa) to 55 bar (55,000 kPa), or 40 bar (40,000 kPa) to 50 bar (50,000 kPa).

[0024] In the implementation scheme, the reaction conditions also include a gas hourly space velocity (GHSV) (measured as volume of feed stream 102 / volume of catalyst per hour) of at least 500 h⁻¹ within the reaction zone 101. -1 Such as at least 1000 hr -1 Such as at least 1200 hr -1 Such as at least 1800 hr -1 Such as at least 2400 hr -1 Such as at least 3000 hr -1 Such as at least 3600 hr -1Such as at least 4200 hr -1 Such as at least 4800 hr -1 Such as at least 5400 hr -1 Such as at least 6000 hr -1 Such as at least 6600 hr -1 Or such as at least 7200 hr -1 In the implementation scheme, the reaction conditions also include GHSV being less than 15000 hr in reaction zone 101. -1 Such as less than 14600 hr -1 Such as less than 14000 hr -1 Such as less than 13400 hr -1 Or, for example, less than 12800hr -1 .

[0025] The hybrid catalyst used in the methods disclosed above will now be described. As previously described, the hybrid catalyst system comprises a metal oxide catalyst component that converts the feed stream into oxidized hydrocarbons and a microporous catalyst component that converts the oxidized hydrocarbons into hydrocarbons.

[0026] In one or more embodiments, the mixed metal oxide catalyst component may be a bulk catalyst or a supported catalyst and may be prepared by any suitable method, such as co-precipitation, impregnation, etc. In embodiments, the mixed metal oxide catalyst component may comprise gallium, lanthanum, or combinations thereof. In embodiments, the mixed metal oxide catalyst component comprises zirconium oxide. In embodiments, the mixed metal oxide catalyst component may comprise gallium, lanthanum, or combinations thereof supported on zirconium oxide. Additional mixed metal oxide catalyst components may be considered based on the product composition determined by the microporous catalyst component. Without being bound by any particular theory, the cage geometry of the pore combination with the microporous catalyst component may partially determine the C2 / C3 carbon molar ratio of the hydrocarbons produced in product stream 103, regardless of the mixed metal oxide catalyst used. It should be understood that any metal in the mixed metal oxide component mixture may be present in multiple oxidation states. It should also be understood that the naming of a particular oxide (e.g., Ga2O3) does not necessarily exclude the presence of additional or different oxides of a given metal (one or more).

[0027] In one embodiment, the mixed metal oxide catalyst components can be reduced within the reactor prior to exposure to the feed stream 102 by exposing them to a conventional reducing gas. In one or more embodiments, the mixed metal oxide catalyst components can be reduced within the reactor when exposed to a reducing gas (such as H2 and CO) in the feed stream 102.

[0028] According to embodiments, the hybrid catalyst comprises a mixture of a mixed metal oxide catalyst component and a microporous catalyst component, the microporous catalyst component being selected from molecular sieves having an 8-MR pore size of less than or equal to 5.1 Å and a cage-bound ring size of less than or equal to 7.45 Å. In embodiments, the microporous catalyst component may comprise a framework type selected from ERI, LEV, DDR, HEU, PHI, STI, NAT, or ATN framework types and combinations thereof, the framework types corresponding to the naming conventions of the International Zeolite Association. In embodiments, the microporous catalyst component may comprise one or more of silica-aluminate or silica-aluminophosphate. It should be understood that in embodiments, both aluminosilicate, aluminosilicate, and silica-aluminophosphate frameworks may be used. In one or more embodiments, the molecular sieve may be H-ERI having a zeolite (ERI) framework type.

[0029] According to the implementation scheme, the microporous catalyst component may contain a SiO2 / Al2O3 molar ratio of less than or equal to 50.0, such as less than or equal to 48.0, less than or equal to 46.0, less than or equal to 44.0, less than or equal to 42.0, less than or equal to 40.0, less than or equal to 38.0, less than or equal to 36.0, less than or equal to 34.0, less than or equal to 32.0, less than or equal to 30.0, less than or equal to 28.0, less than or equal to 26.0, less than or equal to 24.0, less than or equal to 22.0, less than or equal to 20.0, less than or equal to 18.0, less than or equal to 16.0, less than or equal to 14.0, less than or equal to 12.0, or less than or equal to 10.0. In the embodiments, the microporous catalyst component may contain a SiO2 / Al2O3 molar ratio greater than or equal to 1.0, such as greater than or equal to 1.5, greater than or equal to 2.0, greater than or equal to 2.5, greater than or equal to 3.0, greater than or equal to 3.5, greater than or equal to 4.0, or greater than or equal to 4.5.

[0030] Examples of these may include, but are not limited to, ERI embodiments selected from SAPO-17 or SSZ-98; and LEV embodiments, such as SAPO-35 or SSZ-17. Other embodiments may include ERI-LEV symbionts, such as SSZ-105. Combinations of microporous catalyst components having any of the above framework types may also be employed. It should be understood that, depending on the desired product, the microporous catalyst components may have different membered ring pore openings. For example, depending on the desired product, microporous catalyst components with 8-MR to 12-MR pore openings may be used. However, for the production of C2 to C3 hydrocarbons, microporous catalyst components with 8-MR pore openings are used in the embodiments.

[0031] Unbound by any particular theory, it is believed that the pore size (Atlas of zeolite framework types, 6th edition, Elsevier, pp. 381-86, 2007) and cage-limiting ring size (ACS Catalysis, 2019, Vol. 9, p. 6017) can contribute to the desired hydrocarbon product. The pore size may be important for narrowing the product distribution. Additionally, the cage-limiting ring size may be important for enhancing the C2 fraction in the product distribution. The cage-limiting ring size can be equated to the longest axis of the elliptic that can be fitted into the cage of the microporous catalyst component. In embodiments where the microporous catalyst component does not include a cage, the pore size and maximum channel size of the microporous catalyst component can contribute to the desired hydrocarbon product. The pore and cage-limiting ring sizes can be customized to target hydrocarbon products with specific product distributions. This theory is supported by “Cage-Defining Ring: AMolecular Sieve Structural Indicator for Light Olefin Product Distribution from the Methanol-to-Olefins Reaction,” John Hun Kang, Faisal H. Alshafei, Stacey I. Zones, & Mark E. Davis, ACS Catalysis 2019 9(7), 6012-6019 (April 11, 2019).

[0032] As previously described, in embodiments, the molecular sieve of the microporous catalyst component may have 8-MR pores of less than or equal to 5.1 Å. In embodiments, the molecular sieve of the microporous catalyst component may have 8-MR pores of greater than or equal to 1.0 Å, such as greater than or equal to 1.5 Å, greater than or equal to 2.0 Å, greater than or equal to 2.5 Å, greater than or equal to 3.0 Å, greater than or equal to 3.3 Å, greater than or equal to 3.6 Å, greater than or equal to 3.9 Å, greater than or equal to 4.2 Å, greater than or equal to 4.5 Å, or greater than or equal to 4.8 Å. Furthermore, in embodiments, the molecular sieve of the microporous catalyst component may contain cage-bound rings with a size of less than or equal to 7.45 Å. In the embodiments, the molecular sieve of the microporous catalyst component may contain cage-limiting ring sizes greater than or equal to 7.45 Å, such as greater than or equal to 3.00 Å, greater than or equal to 4.00 Å, greater than or equal to 5.00 Å, greater than or equal to 6.00 Å, greater than or equal to 6.25 Å, greater than or equal to 6.50 Å, greater than or equal to 6.75 Å, greater than or equal to 7.00 Å, and greater than or equal to 7.25 Å.

[0033] As further demonstrated by the following examples, the microporous catalyst component can undergo ion exchange before being combined with the mixed metal oxide catalyst component. Unbound from any particular theory, ion exchange can alter the properties of the microporous catalyst component (and thus the overall hybrid catalyst) by increasing the acidity of the microporous catalyst component through the replacement of metal atoms (such as, but not limited to, potassium or sodium) with hydrogen. This increased acidity of the microporous catalyst component can thus alter the chemical properties of the hybrid catalyst, allowing the method to be tailored to form the desired product.

[0034] The mixed metal oxide catalyst component and the microporous catalyst component of the hybrid catalyst can be mixed together by any suitable means, such as by physical mixing—e.g., shaking, stirring, or other agitation. In embodiments, the mixed metal oxide catalyst component and the microporous catalyst component can be present as a single-formulated catalyst. The mixed metal oxide catalyst component and the microporous catalyst component can be present in reaction zone 101 at a weight / weight (wt / wt) ratio (mixed metal oxide catalyst component: microporous catalyst component) in the range of 0.1:1 to 10:1 (e.g., 0.5:1 to 9:1), typically present as a hybrid catalyst in a catalyst bed.

[0035] While the hybrid catalysts described herein are applicable to methods other than syngas to hydrocarbon systems, it has been found that hybrid catalysts are not directly transferable between various methods. That is, a catalyst that is effective in one method may exhibit poor performance in another. For example, a catalyst showing satisfactory performance in the C2 / C3 carbon molar ratio in a methanol to olefins process may not be directly transferable to a syngas to hydrocarbon process, where the same catalyst may not exhibit the same satisfactory performance. For instance, a hybrid catalyst comprising SSZ-13 with a CHA topology may not exhibit the same product distribution in different systems (such as MTO) providing a syngas to hydrocarbon system.

[0036] Example The implementation scheme is further illustrated by the following examples.

[0037] Example 1 :have H-ERI Hybrid catalysts with microporous catalyst components In Example 1, the microporous catalyst component was prepared from bufosite. Bufosite from Minerals Research, PO Box 591, Clarkson, NY 14430 was collected from Eastgate, Nevada. Approximately 10 g of bufosite 25220 was placed in a flint glass jar equipped with a stir bar. Then, 100 mL of 0.1 M ammonium acetate was added. A series of three ion exchanges was performed. After each ion exchange, the solid was recovered by filtration, washed, and resuspended. In the first exchange, the bufosite and ammonium acetate were stirred at ambient temperature for eighteen hours. In the second exchange (after filtration, washing, and resuspending), the bufosite and ammonium acetate were stirred at ambient temperature for five hours. In the third exchange (after filtration, washing, and resuspending), the bufosite and ammonium acetate were again stirred at ambient temperature for eighteen hours. After the third and final exchange, the final product was collected by filtration, washed, and then dried at 90°C. After drying, the product was calcined in air by increasing the temperature to 550°C at a rate of 2.5°C / min. The temperature was then maintained at 550°C for four hours. The calcined powder was then compacted and sized to 60-100 mesh to form the H-ERI microporous catalyst component.

[0038] To prepare the mixed metal oxide catalyst composition, 4.40 mL of gallium stock solution (gallium(III) nitrate hydrate with C=2.0 M in deionized water), 1.76 mL of lanthanum stock solution (lanthanum(III) nitrate hexahydrate with C=1.5 M in deionized water), and 2.86 mL of impregnation solution in deionized water were mixed. Then, 20 g of a catalyst with 100 M... 2A 60-80 mesh ZrO2 support (NORPRO© SZ31164) with a Brunauer-Emmett-Teller specific surface area, 0.41 mL / g pore volume (measured by deionized water), and 100% monoclinic phase (measured by XRD) was placed in a glass vial. The impregnation solution was then added dropwise to the ZrO2 support while shaking. Once the impregnation solution and ZrO2 support were combined, the mixture was dried in static air at 120°C. The product was then calcined by increasing the temperature to 120°C at a rate of 2.0°C / min. After holding the temperature at 120°C for two hours, the temperature was increased again, this time to 550°C at a rate of 3.0°C / min. After holding the temperature at 550°C for four hours, the product was cooled to room temperature over a two-hour period. After calcination, the catalyst was re-sieved to a 60-100 mesh size to remove any fine particles. As determined by X-ray fluorescence, the mixed metal oxide catalyst composition has a composition of 3.1 wt% Ga, 1.5 wt% La, 67.3 wt% Zr, 2.4 wt% Hf and 25.7 wt% O.

[0039] To prepare the hybrid catalyst, the microporous catalyst component and the mixed metal oxide were mixed and shaken for thirty seconds.

[0040] Example 2 :have LZ-220 Hybrid catalysts with microporous catalyst components To prepare the microporous catalyst component, the H-ERI microporous catalyst component of Example 1 was further processed to produce the LZ-220 microporous catalyst component. LZ-220 is further described in U.S. Patent No. 4,503,023, which is incorporated herein by reference. First, an ammonium hexafluorosilicate stock solution was prepared by dissolving 8.0 g of (NH4)2SiF6 in 250 mL of high-purity water. Then, 5.0 g of ion-exchanged NH4-ERI (i.e., the microporous catalyst component of Example 1) was suspended in 100 mL of high-purity water in a flint glass jar with a stir bar, while vigorous stirring. While the NH4-ERI solution was heated to 80°C, 50 mL of ammonium hexafluorosilicate solution was added to the NH4-ERI solution. The resulting mixture was then heated to 90°C and maintained at 90°C for three hours. After cooling the solution for one hour, the solid was collected by filtration and washed. The final solid was then dried at 90°C. The prepared microporous catalyst component was then dried and calcined in air by increasing the temperature to 550°C at a rate of 2.5°C / min. The temperature was then maintained at 550°C for four hours. The calcined powder was then compacted and sized to 60-100 mesh to form the LZ-220 microporous catalyst component.

[0041] The mixed metal oxide catalyst component was prepared in the same manner as in Example 1. Finally, the microporous catalyst component and the mixed metal oxide were mixed and shaken for thirty seconds to form a hybrid catalyst.

[0042] Comparative example 1 :have SAPO-34 Hybrid catalysts with microporous catalyst components To prepare the SAPO-34 microporous catalyst component, the microporous catalyst component was synthesized according to the procedure of U.S. Patent 4,440,871A, which is incorporated herein by reference. The formed microporous catalyst component was then calcined in air by increasing the temperature from 25°C to 600°C at a rate of 5°C / min. The temperature was held at 600°C for four hours, and then the temperature was lowered to 25°C over the four-hour period. The calcined powder was then compacted and sized to 60-100 mesh to form the SAPO-34 microporous catalyst component.

[0043] In Comparative Example 1, the mixed metal oxide catalyst composition and the preparation of the hybrid catalyst were the same as in Examples 1 and 2.

[0044] Comparative example 2 :have SSZ-39 Hybrid catalysts with microporous catalyst components The SSZ-39 sample was a readily available commodity (purchased from ChinaCatalyst Holding Co., Ltd.). The structure and crystallinity of the SSZ-39 microporous catalyst component were confirmed by XRD. The sample was calcined in air using the same procedure as Comparative Example 1 and then sieved to a size of 60-100 mesh to form the SSZ-39 microporous catalyst component.

[0045] In Comparative Example 2, the mixed metal oxide catalyst composition and the preparation of the hybrid catalyst were the same as in Examples 1 and 2.

[0046] Comparative example 3 :have SAPO-11 Hybrid catalysts with microporous catalyst components SAPO-11 samples were readily available commercially (purchased from ChinaCatalyst Holding Co., Ltd.). The structure and crystallinity of the SAPO-11 microporous catalyst component were confirmed by XRD. The samples were calcined in air using the same procedure as Comparative Example 1 and then sieved to a size of 60-100 mesh to form the SAPO-11 microporous catalyst component.

[0047] In Comparative Example 3, the mixed metal oxide catalyst composition and the preparation of the hybrid catalyst were the same as in Examples 1 and 2.

[0048] Comparative example 4 :have ZSM-5 Hybrid catalysts with microporous catalyst components The ZSM-5 sample was a readily available commercial product (purchased from China Catalyst Holding Co., Ltd.). The structure and crystallinity of the ZSM-5 microporous catalyst component were confirmed by XRD. The sample was calcined in air using the same procedure as Comparative Example 1 and then sieved to a size of 60-100 mesh to form the ZSM-5 microporous catalyst component.

[0049] In Comparative Example 3, the mixed metal oxide catalyst composition and the preparation of the hybrid catalyst were the same as in Examples 1 and 2.

[0050] The composition of the microporous catalyst components of Examples 1-2 and Comparative Examples 1-4. Table 1 shows the composition of the microporous catalyst components of Examples 1-2 and Comparative Examples 1-4.

[0051] Table 1. Composition of Examples 1-2 and Comparative Examples 1-4 In addition, the results of Examples 1-2 and Comparative Examples 1-4 are shown in Table 2.

[0052] Table 2. Structural properties of Examples 1-2 and Comparative Examples 1-4 : Catalytic tests of Examples 1-2 and Comparative Examples 1-4 Catalytic testing was conducted in either a tubular stainless steel reactor with an inner diameter of 3 mm or a quartz fixed-bed reactor with an inner diameter of 2 mm. The stainless steel reactor had a metal glass frit at the bottom to hold the catalyst bed. The quartz reactor had a quartz sheet topped with wool at the bottom to secure the catalyst bed. In the catalytic testing, the hybrid catalyst was loaded onto the reactor and the following procedure was followed: nitrogen gas was flowed into the reactor as the temperature increased from 25°C to the reaction temperature (increased by 5°C / min). Similarly, the pressure was increased from ambient conditions to the reaction pressure. The nitrogen gas flow was then replaced with a syngas flow. The syngas flow was continued to purge for one hour, after which gas chromatography analysis was initiated. After the set run time duration, the syngas flow was replaced with a nitrogen flow as the reactor returned to ambient temperature and pressure.

[0053] Two different reaction conditions were used in the catalytic tests of Examples 1-2 and Comparative Examples 1-4, as shown in Table 3.

[0054] Table 3. Reaction conditions Finally, Table 4 shows the catalytic data for various catalytic tests in Examples 1-2 and Comparative Examples 1-4. Additionally, Table 5 details the product selectivity. Products were analyzed using gas chromatography. Online analysis of components (N2, H2, He, CO, CO2, C1-C5 alkanes, C2-C5 alkenes, methanol, and dimethyl ether) was performed periodically to monitor reaction progress. In all experiments, the mass balance based on carbon was 100 ± 5%.

[0055] Table 4. Catalytic data of Examples 1-2 and Comparative Examples 1-4 Table 5. Selectivity of Examples 1-2 and Comparative Examples 1-4 Table 5. Selectivity of Examples 1-2 and Comparative Examples 1-4 (continued) As can be seen from Tables 4 and 5, hybrid catalysts (Examples 1 and 2) containing microporous catalyst components with 8-MR pore openings less than or equal to 5.1 Å and cage-bound ring sizes less than or equal to 7.45 Å can convert syngas into hydrocarbons with high C2 and C3 selectivity (e.g., based on a total hydrocarbon fraction in the product stream greater than 40 C mol%) and a C2 / C3 carbon molar ratio greater than 1.0. Conversely, hybrid catalysts (Comparative Examples 1-4) not containing microporous catalyst components with 8-MR pore openings less than or equal to 5.1 Å and cage-bound ring sizes less than or equal to 7.45 Å cannot convert syngas into hydrocarbons with high C2 and C3 selectivity (e.g., based on a total hydrocarbon fraction in the product stream greater than 40 C mol%) and a C2 / C3 carbon molar ratio greater than 1.0.

[0056] Calculation of catalyst performance in examples and comparative examples Carbon monoxide conversion rate (X) CO [C mol%]) is defined as the ratio between the molar flow of carbon monoxide leaving the reaction zone and the flow of carbon monoxide entering the reaction zone. The formula used to calculate the carbon monoxide conversion rate is shown in Equation 1: (Equation 1) Where F CO,进入 It is the molar flow of carbon monoxide entering the reaction zone, measured in mol / h, and F CO,离开 It is the molar flow of carbon monoxide leaving the reaction zone, measured in mol / h.

[0057] The selectivity of component i [C mol%] was measured as the average of all data points at the run times specified in Tables 3 and 4. This was used for calculations. i The formula for the selectivity of the components is shown in the following Equation 2: (Equation 2) Where n i yes i The number of carbon atoms in the component, F i The components leaving the reaction zone are measured in mol / h. i molar flux, F CO,进入 It is the molar flow rate of carbon monoxide entering the reaction zone, measured in mol / h, and F CO,离开 It is the molar flow rate of carbon monoxide leaving the reaction zone, measured in mol / h.

[0058] The carbon balance ratio (CB) [C mol%] is the ratio of the total amount of carbon entering the reaction zone as carbon monoxide to the amount of carbon leaving the reaction zone as carbon monoxide and carbon-containing products. The formula used to calculate the carbon balance ratio is shown in Equation 3: (Equation 3) Where n i yes i The number of carbon atoms in the component, F i The components leaving the reaction zone are measured in mol / h. i molar flux, F CO,进入 It is the molar flow rate of carbon monoxide entering the reaction zone, measured in mol / h.

[0059] The ratio C2 / C3 is calculated using Equation 4 as shown below: (Equation 4) Where F 丙烯 and F 丙烷 The molar flow rates of propylene and propane, respectively, measured in mol / h, and F 乙烯 and F 乙烷 These are the molar flow rates of ethylene and ethane, measured in mol / h, respectively.

[0060] It will be apparent to those skilled in the art that various modifications and variations can be made to the embodiments described herein without departing from the spirit and scope of the claimed subject matter. Therefore, this specification is intended to cover modifications and variations to the various embodiments described herein, provided that such modifications and variations fall within the scope of the appended claims and their equivalents.

Claims

1. A method for preparing C2 to C3 hydrocarbons, the method comprising: A feed stream containing hydrogen and carbon-containing gases selected from the group consisting of carbon monoxide, carbon dioxide, and mixtures thereof is introduced into the reaction zone of the reactor. as well as In the reaction zone, the feed stream is converted into a product stream containing C2 to C3 hydrocarbons in the presence of a hybrid catalyst, the hybrid catalyst comprising: Mixed metal oxide catalyst components; and A microporous catalyst component comprising 8-MR pore openings with a size less than or equal to 5.1 Å and cage-bound rings with a size less than 7.45 Å, wherein: The C2 / C3 carbon molar ratio of the product stream is greater than or equal to 0.

7. The mixed metal oxide catalyst component contains gallium supported on zirconium oxide.

2. The method according to claim 1, wherein the microporous catalyst component comprises one or more of aluminosilicates or aluminosilicate phosphates (SAPO).

3. The method according to claim 1 or 2, wherein the microporous catalyst component comprises a tufted zeolite or intercalated chalcogenide structure.

4. The method according to claim 1 or 2, wherein the microporous catalyst component comprises one or more of SAPO-17, SAPO-35, LZ-220, SSZ-17, SSZ-98, SSZ-105, SAPO-67 or combinations thereof.

5. The method according to claim 1 or 2, wherein the microporous catalyst component comprises a SiO2 / Al2O3 molar ratio of less than or equal to 50.

0.

6. The method according to claim 1 or 2, wherein the metal component accounts for 0.1% to 10.0% by weight of the metal oxide catalyst component.

7. The method according to claim 1 or 2, wherein the reaction zone is operated at a temperature of 370°C to 470°C.

8. The method according to claim 1 or 2, wherein the reaction zone is operated at a pressure of 20 bar to 70 bar.

9. The method according to claim 1 or 2, wherein the reaction conditions of the method include a reaction time of more than 500 hours. -1 The air space velocity (GHSV).

10. The method according to claim 1 or 2, wherein the hybrid catalyst comprises a metal oxide catalyst component to a microporous catalyst component in a weight ratio of 0.1:1 to 10:

1.

11. The method according to claim 1 or 2, wherein the product stream comprises C2 to C3 hydrocarbons with a total hydrocarbon fraction greater than 40 mol% based on the total hydrocarbon fraction in the product stream.

12. The method according to claim 1 or 2, wherein the C2 / C3 carbon molar ratio of the product stream is greater than or equal to 1.

0.

13. The method according to claim 1 or 2, wherein the C2 to C3 hydrocarbons are substantially composed of olefins.

Citation Information

Patent Citations

  • Crystalline silicoaluminophosphates

    US4440871A

  • Silicon substituted zeolite compositions and process for preparing same

    US4503023A

  • Conversion of carbon monoxide, carbon dioxide, or a combination thereof over hybrid catalyst

    CN106660894A

  • Processes and systems for achieving high carbon conversion to desired products in a hybrid catalyst system

    CN110072831A